EFL Studentsâ€™ Pronunciation Problems in Presenting Thesis Proposal at Tertiary Level of English Department - Rahman, Arif; Tralala, Lalu Nawasier (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2021)
The aim of the research is to investigate EFL Studentsâ€™ Pronunciation Problems in Presenting Thesis Proposal at Tertiary Level of English Department. This qualitative study reported in this article focused on segmental features problems. The instruments used to collect the data needed in this study were the researcher, recording, and Dictionary. The data analysis covered consonant and vowel pronunciation problems. was based on the theories of phonetics proposed by George Yule and Jacobs, which embraces voicing, manner of articulation and place of articulation for English consonant production and the tongue part and position, sound length, and mouth forming for English vowel production. The result of the study shows that the research subject encountered a number of segmental pronunciation problems consisting of consonants and vowels including pure vowels and diphthongs. Furthermore, this research revealed that the problem with consonant sounds were the substitution of the sounds [v], [Ã°], [Î¸], [tâˆ«], [Ê’], [Êƒ] [z] and the deletion of the Â sounds [k], [É¡], [t], and [s]. The problem with pure vowel sounds were the substitution of the sound [Éª], [iË], [É›], [ÊŠ], [ÊŒ], [ÉœË], [É’], [É”Ë] and [É™] and the insertion of the sound [É™] between two consonant sounds. The problem with diphthongs were: the monophthongization of the sound [aÉª], [aÊŠ], [eÉª], [ÉªÉ™], [É™ÊŠ], and the replacement of the sounds [eÉª] and [ÉªÉ™] with other diphthongs. It is suggested for the next researchers to investigate pronunciation problems related to supra-segmental aspects and phonemic opposition. and factors driving pronunciation problems in the EFL Classroom setting.